Peningkatan Peran Serta Tokoh Agama Dalam Pembangunan Berbagai Sektor Kehidupan Di Desa - Syarif, M.; Yaqin, Ainul (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
So far, the role of religious figures in the environment has always been anchored in religious roles that are limited to bringing moral messages as well as peace missions in the event of horizontal conflict. It is very rare for religious figures to play an active role in the material development of the village, let alone being actively involved in the village government structure. Until now, the role of these religious figures as part of the village elite has not been explored optimally to boost the pace of the village development process. This community service program aims to increase the role of religious figures in Gayaman village not only limited to religious roles alone, but also have a significant role in material development that involves decision-making at the village structural level. Along with the issuance of Law No. 3 of 2024 junto Law No. 6 of 2016 concerning Villages concerning villages which emphasize the mandatory participation of village communities, the role of these elites becomes very significant, because it is through them that the encouragement for the community to participate in village development is strengthened. This community service program is implemented using the Participatory Action Research (PAR) method which involves participation, in this case, religious figures in Gayaman village to take active action for the purpose of social transformation. From this service, it is obtained that the role of these religious figures (as part of the village elite) focuses more on their influence in moral development and only in a small portion they play a role in physical material development policies. It is recommended that the government, both central and regional, can establish stricter regulations in positioning the role of religious figures in the village precisely for the sake of the smooth development itself.